Analisis Keterlambatan Penyandaran Kapal Tanker di Terminal Khusus Pertamina Refinery Unit II Dumai - Octi Avriani (Sekolah Tinggi Manajemen Transportasi (STMT Malahayati Jakarta), 2023)
PERTAMINA Refinery Unit II Dumai is located in the Riau Islands region. The objectives of this research are (1). To find out the obstacles that occur when berthing ships at the special terminal PERTAMINA Refinery Unit II Dumai and (2). To find out the efforts made to overcome obstacles that occur when berthing ships at the special PERTAMINA Refinery Unit II Dumai terminal. This research was carried out at PT. PERTAMINA Refinery Unit II Dumai, this research was carried out from August 2023 to August 2024. The data source was obtained through descriptive research methods with a qualitative approach, with data collection analysis techniques based on the results of observation and documentation. The research results show that the implementation of the tanker berthing process at the special PERTAMINA Refinery Unit II Dumai terminal is still experiencing delays. There are several problems that cause delays, including only 1 jetty capacity so you have to queue, weather that does not allow for the docking process, smaller land tank capacity, and the inability to carry out the docking process at night.